Stereoselective Bacterial Metabolism of Antibiotics in Environmental Bacteria – A Novel Biochemical Workflow - Elder, Felicity C. T.; Feil, Edward J.; Pascoe, Ben; Sheppard, Samuel K.; Snape, Jason; Gaze, William H.; Kasprzyk-Hordern, Barbara (Frontiers in Microbiology, 2021)
Although molecular genetic approaches have greatly increased our understanding of the evolution and spread of antibiotic resistance genes, there are fewer studies on the dynamics of antibiotic – microbial (A-M) interactions, especially with respect to stereochemistry. Addressing this knowledge gap requires an interdisciplinary synthesis, and the development of sensitive and selective analytical tools. Here we describe SAM (stereoselective antimicrobial metabolism) workflow, a novel interdisciplinary approach for assessing bacterial resistance mechanisms in the context of A-M interactions that utilise a combination of whole genome sequencing and mass spectrometry. Chloramphenicol was used to provide proof-of-concept to demonstrate the importance of stereoselective metabolism by resistant environmental bacteria. Our data shows that chloramphenicol can be stereoselectively transformed via microbial metabolism with R,R-(-)-CAP being subject to extensive metabolic transformation by an environmental bacteria strain. In contrast S,S-(+)-CAP is not metabolised by this bacteria strain, possibly due to the lack of previous exposure to this isomer in the absence of historical selective pressure to evolve metabolic capacity.